Gestão cooperativa, ambiente institucional e sociocultural: o caso Brasil-Paraguai - Tarifa, Marcelo Resquetti (2014)
The purpose of this thesis was to analyze the influence of institutional and socio-cultural environment in the cooperative management of the C.VALE Agroindustrial Cooperative, compared to the most representative units located in Parana, Brazil, and the ones located in Paraguay. Therefore, the following research problem was established: the institutional and socio-cultural environments influence the cooperative management of C.VALE, in comparison to the Paraná and Paraguay units? As possible solutions to the problem, two hypotheses were related: H1 The cooperative units located in Paraná, Brazil, have a heterogeneous management influenced by the formal and informal rules, an internal culture focused on grouping and practices that attend the generation of social capital in the environment where they operate; H2 The cooperative units located in Paraguay have a homogeneous management influenced only by the formal rules, an internal culture focused on the hierarchy of the entity itself, and practices that attend to the social capital generation in the environment that they operate. In relation to the methodology of this study, it was classified, regarding its objectives, as exploratory and explanatory; in relation to its procedures, as bibliographic and as a case study; and to its problem approach, as qualitative. Each analyzed environment has been theoretically based to make the comparison between the cooperative units situated in Paraná and the others, in Paraguay. The analyses of the institutional environment were based on the New Institutional Economics, with emphasis on the Douglass North's theory (1990) about the institutions and occurred with in loco interviews in each cooperative unit that was covered by the sample. The analyzes of the cultural environment were based on the characterization of the organizational culture of each cooperative unit, according to the Competing Value Model, developed by Cameron and Quinn (1998), that typifies it in group culture, innovative, market and hierarchical, applied to the same managers, through online electronic questionnaire . The analyses of the social environment were based on the theoretical concept of social capital and the respective characteristics identified in the units by adapting the model proposed by the World Bank study group (BM), prepared by Grootaert et al. (2003), through the content analyses of the interviews. As a result to the established problem it was concluded that, even C.VALE being a single cooperative, there are influences of the institutional and the socio-cultural environment in the process of management of the cooperative units in Paraná and Paraguay. However, in relation to the established hypotheses, both were rejected. In the former, the identified characteristics clearly distinguish the Brazilian units, and, in the second one, it´s not possible to affirm that the management of the Paraguayan units are homogeneous in consideration of the proximity of features with the ones situated in Paraná. Finally, according to the grouping proposal of the coperative units based on the collected data and in the use of the NVIVO® software of qualitative analyzes, four specific clusters were identified: Cluster 1 - Campina da Lagoa and Forest Units; Cluster 2 - Campo Mourão and Guarapuava Units; Cluster 3 - Maripá, São Jorge do Ivaí, Central Administration and Palotina Units; Cluster 4 - Mamborê, São João do Ivaí, Paraguay and Terra Roxa Units. The four groups generated through qualitative analysis by data approach corroborated whith the respective analyzes developed for each environment explored in the research, with emphasis on the cross-borderism of some features present in Brazilian and Paraguayan units.